Evaluation of the precision ID mtDNA whole genome panel on two massively parallel sequencing systems. (September 2018) - Woerner, August E.; Ambers, Angie; Wendt, Frank R.; King, Jonathan L.; Moura-Neto, Rodrigo Soares; Silva, Rosane; Budowle, Bruce
Highlights: Concordance assessment of the Precision ID mtDNA whole genome panel on the Ion S5 and the MiSeq FGx. Estimation of amplicon haplotypes using read-backed phasing. Detection and mitigation of the effects of nuclear mitochondrial sequences. Abstract: Sequencing whole mitochondrial genomes by capillary electrophoresis is a costly and time/labor-intensive endeavor. Many of the previous Sanger sequencing-based approaches generated amplicons that were several kilobases in length; lengths that are likely not amenable for most forensic applications. However, with the advent of massively parallel sequencing (MPS) short-amplicon multiplexes covering the entire mitochondrial genome can be sequenced relatively easily and rapidly. Recently, the Precision ID mtDNA Whole Genome Panel (Thermo Fisher Scientific by Applied Biosystems™) has been introduced. This panel is composed of 162 amplicons (in two multiplexes) that are considerably smaller in length (∼163bp) and thus are more amenable to analyzing challenged samples. This panel was evaluated on both the Ion S5™ System (Thermo Fisher Scientific) and the MiSeq™ FGx Desktop Sequencer (Illumina). A script was developed to extract phased haplotypes associated with these amplicons. Levels of read-depth were compared across sequencing pools and between sequencing technologies and haplotype concordances were assessed. Given modest thresholds on read depth, the haplotypes identified by either technology were consistent. Nuclear mitochondrial sequences (Numts) were also inferred, and the effect of different mapping strategies commonly used to filter out Numts were contrasted. Some Numts are co-amplified with this amplification kit, and while the choice of reference sequence can mitigate some of these effects, some data from the mitochondrial genome were lost in the process in this study. This study demonstrates that the Ion and MiSeq platforms provide consistent haplotype estimation of the whole mitochondrial genome, thus providing further support for the reliability and validity of the Precision ID mtDNA Whole Genome Panel.